109 Chemogenetic silencing of corticotropin releasing factor neurons in the paraventricular nucleus: the effect on post-stress sleep. (3rd May 2021) - Gvilia, Irma; Kumar, Sunil; McGinty, Dennis; Szymusiak, Ronald
Abstract: Introduction: We have previously shown that pharmacological elevation of corticotropin releasing factor (CRF) signaling in the brain results in exacerbation of sleep disturbances evoked by the exposure of rats to an acute stressor, the dirty cage of a male rat. In the present study we (1) assessed wake-sleep behavior of mice after the exposure to the dirty cage stress paradigm, and (2) examined the effect of chemogenetic silencing of CRF neurons in the hypothalamic paraventricular nucleus (PVN) on sleep occurring following the exposure to this stressor. Methods: First, a group of mice (n=12) was implanted with EEG/EMG electrodes. In two weeks, post-surgery, six mice were transferred to dirty cages of male rats and recorded for 24 hours. Control mice were transferred to clean cages. In the second study, a group of CRF-ires-cre mice (n=8) received bilateral injections of AAV-hSyn-DIO-hM4Di-mCherry targeting the PVN. The other group of CRF-ires-cre mice (n=8) was injected AAV-hSyn-DIO-mCherry (control vector). All mice were implanted with EEG/EMG electrodes. Dirty cage experiments were started following a 4-week postsurgical period to allow gene recombination and expression. Mice were subjected to intraperitoneal (IP) administration of clozapine-n-oxide (CNO; 3 mg/kg) at ZT1, placed into dirty cages, and recorded for post-stress sleep. Results: Results: In mice expressing hM4Di inhibitory DREADDs (designer receptors activated by designer drugs) versus mice injected with control AAV, IP CNO (3 mg/kg) resulted in a significant decrease of post-stress sleep onset latency, decrease of time spent in wakefulness (first hour, 74±5.3 vs. 89±11.0, second hour, 37.2±10.3% vs. 81.3±9.3%; third hour, 40.1±3.3% vs. 47.1±14.3%; fourth hour, 44.4±6.0 vs. 55.5±9.9), and increase in non-rapid eye movement (NREM) sleep time (26.0±5.4% vs. 11.0±11.1%; 62.8%±9.8 vs. 18.7 ± 9.6%; 59.9±3.2% vs. 52.9±14.5%; 55.6±6.2 vs. 44.5±10.0). The hM4Di expressing mice exhibited longer episodes of NREM sleep, compared to mice injected with control AAV (first hour, 133.3±80.1sec vs. 21±1.7sec; second hour, 43256±83.4sec vs. 73.5±44.1sec; third hour, 459.2±139.8sec vs. 139±80.6sec; fourth hour, 233.1±82.6sec vs. 190±72.3sec). Conclusion: Chemogenetic silencing of CRF neurons in the PVN attenuates acute stress-induced sleep disturbance in mice. Support (if any): Supported by Department of Veterans Affairs Merit Review Grant # BX00155605 and SRNSF (Georgia) grant FR-18-12533